2013
DOI: 10.1160/th12-06-0441
|View full text |Cite
|
Sign up to set email alerts
|

Analysing responses to aspirin and clopidogrel by measuring platelet thrombus formation under arterial flow conditions

Abstract: High residual platelet aggregability and circulating platelet-monocyte aggregates in patients administered aspirin and clopidogrel are associated with ischaemic vascular events. To determine the relevance of these factors with residual thrombogenicity, we measured platelet thrombus formation using a microchip-based flow-chamber system in cardiac patients receiving aspirin and/or clopidogrel, and evaluated its correlation with agonist-inducible platelet aggregation and platelet-monocyte aggregates. Platelet thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 32 publications
4
53
0
Order By: Relevance
“…These features allowed us to broaden the use of this system to assess blood samples without any reference to the drugs used. The utility of the T-TAS for evaluating clotting status has been reported in experimental animals [31], healthy subjects [32][33][34], and a small population of patients [19,35]. The present study confirmed its usefulness in CAD patients.…”
Section: Discussionsupporting
confidence: 82%
“…These features allowed us to broaden the use of this system to assess blood samples without any reference to the drugs used. The utility of the T-TAS for evaluating clotting status has been reported in experimental animals [31], healthy subjects [32][33][34], and a small population of patients [19,35]. The present study confirmed its usefulness in CAD patients.…”
Section: Discussionsupporting
confidence: 82%
“…e l s e v i e r . c o m / l o c a t e / i j c a r d thrombogenic surfaces [4,5,8]. One chip, the platelet (PL)-chip, contains 25 capillary channels (40 μm wide × 40 μm deep) coated with type I collagen.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The microchip flow-chamber system, T-TAS ® (Fujimori Kogyo, Kanagawa, Japan) was utilized with a minor modification according to the protocol proposed by Hosokawa et al [7,9] to analyze the flow-based thrombus formation. Evaluation of platelet thrombus formation was performed with type 1 collagen-coated PL (platelet)-chips (Nitta Gelatin, Osaka, Japan).…”
Section: Microchip Flow-chamber Systemmentioning
confidence: 99%
“…In particular, a newly automated microchip flow-chamber system (total thrombus-formation analysis system, T-TAS ® ) has been recently developed, and some groups have already reported on the comprehensive assessment for hemostatic functions of anti-thrombotic or anti-platelet drugs [7][8][9], hemodilution at cardiopulmonary bypass [10], coagulant bleeding disorder such as hemophilia [11] and von Willebrand disease [12]. This automated device has advantages in evaluating thrombus formation quantitatively in whole blood.…”
Section: Introductionmentioning
confidence: 99%